Isotretinoin — 40 Years in Dermatology - Alexey V. Samtsov (Vestnik Dermatologii i Venerologii, 2020)
The article provides a review of the literature on isotretinoin (Isotretinoin Lidose), which for almost 40 years has been the most effective treatment for moderate forms of acne. The article sets out modern ideas about the mechanism of action of the drug, as well as the evolution of treatment algorithms, as well as the evolution of algorithms for influencing people, which reduces the risk of adverse events. Data on the efficacy and safety of isotretinoin for acne and other dermatoses are provided.